Implementation of Healthy Lifestyle and Balanced Diet in Pampang Village Community for Central Obesity Prevention - Nurachma, Evy; Latianingsih, Nining; Khodijah, Upus Piatun; Muhiban, Ayi; Milasari, Lisa Astria (Pascasarjana Universitas Mataram, 2026)
Central obesity is a primary risk factor for various non-communicable diseases (NCDs), such as type 2 diabetes mellitus and hypertension, with its prevalence steadily increasing due to sedentary lifestyles and imbalanced diets. The community in Pampang Village, Samarinda, faces challenges of nutritional transition characterized by high consumption of processed foods and low physical activity. This Community Service (PKM) activity aims to enhance nutritional literacy and community awareness of the prevention of central obesity by implementing the Isi Piringku (My Plate) balanced diet guidelines. The implementation method involved three stages: awareness through anthropometric health screening (BMI and waist circumference), capacity building through interactive counseling and local food demonstrations, and empowerment through active lifestyle mentoring. The activity involved 45 participants, predominantly from the productive age group and the elderly. Screening results revealed that 60% of participants (27 individuals) suffered from central obesity. The educational intervention significantly improved participants' knowledge, with the average score increasing from 55 (pre-test) to 88 (post-test). The study concludes that community-based health interventions utilizing personal screening and visual education are effective in enhancing community understanding of early detection and dietary changes to reduce the risk of central obesity at the village level.